1997
DOI: 10.1148/radiology.205.3.9393537
|View full text |Cite
|
Sign up to set email alerts
|

Obstructed nasolacrimal duct system in epiphora: long-term results of dacryocystoplasty by means of balloon dilation.

Abstract: The long-term results of dacryocystoplasty, followed if necessary by repeat dacryocystoplasty, are good. Dacryocystoplasty is a safe and simple procedure and could become the treatment of choice for epiphora due to obstruction of the nasolacrimal ducts. Dacryocystorhinostomy is indicated when dacryocystoplasty or repeat dacryocystoplasty fails or when dacryocystoplasty is contraindicated (e.g., in anatomic malformations in the lacrimal duct or bony canal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 0 publications
2
28
0
1
Order By: Relevance
“…The most encouraging long-term result was reported by Janssen et al 11 for the management of subcanalicular obstructions of LDS with 70 and 81% of primary and secondary patency rates, respectively. However, there are less favourable long-term patency rates for the management of idiopathic canalicular and subcanalicular LDS obstructions, reported between 20 and 35.5%.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The most encouraging long-term result was reported by Janssen et al 11 for the management of subcanalicular obstructions of LDS with 70 and 81% of primary and secondary patency rates, respectively. However, there are less favourable long-term patency rates for the management of idiopathic canalicular and subcanalicular LDS obstructions, reported between 20 and 35.5%.…”
Section: Discussionmentioning
confidence: 80%
“…There were studies demonstrating better initial results in partial obstructions, but their long-term results did not maintain that difference. 8,10 Jansen et al 11 showed that partial obstructions have better outcome in both initial and longterm followup period when compared to the complete obstructions. In our previous study, we achieved initial success in all cases with partial obstruction, and it was 56.8% in complete obstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended after failure of external dacryocystorhinostomy (WAITE et al 1993), after failure of balloon dilatation, and preoperatively before endoscopic transnasal dacryocystorhinostomy. When an obstruction is detected on digital subtraction dacryocystography and cannot be easily passed with a guidewire, CT dacryocystography should be performed prior to any balloon dilatation (JANSSEN et al 1997). In some cases pathology can be detected, such as malignant tumors of the lacrimal drainage system or surrounding area, benign tumors of the lacrimal drainage system or nose, and granulomas, such as in Wegener's granulomatosis or sarcoidosis.…”
Section: Indications For Ct Dacryocystographymentioning
confidence: 99%
“…DCR). These patients were treated instead with dacryocystoplasty (DCP) – balloon dilatation of the nasolacrimal duct (NLD) [5, 6, 7, 8]– and temporary stent placement [9, 10]. …”
Section: Introductionmentioning
confidence: 99%